Assessment of measles immunity among infants in Maputo City, Mozambique - Manhiça Ivan; Zango Arlinda; Mussá Tufária; Holm-Hansen Carol; Jani Jagrati V; Bjune Gunnar; Jani Ilesh V (BMC, 2008)
Abstract Background The optimum age for measles vaccination varies from country to country and thus a standardized vaccination schedule is controversial. While the increase in measles vaccination coverage has produced significant changes in the epidemiology of infection, vaccination schedules have not been adjusted. Instead, measures to cut wild-type virus transmission through mass vaccination campaigns have been instituted. This study estimates the presence of measles antibodies among six- and nine-month-old children and assesses the current vaccination seroconversion by using a non invasive method in Maputo City, Mozambique. Methods Six- and nine-month old children and their mothers were screened in a cross-sectional study for measles-specific antibodies in oral fluid. All vaccinated children were invited for a follow-up visit 15 days after immunization to assess seroconversion. Results 82.4% of the children lost maternal antibodies by six months. Most children were antibody-positive post-vaccination at nine months, although 30.5 % of nine month old children had antibodies in oral fluid before vaccination. We suggest that these pre-vaccination antibodies are due to contact with wild-type of measles virus. The observed seroconversion rate after vaccination was 84.2%. Conclusion These data indicate a need to re-evaluate the effectiveness of the measles immunization policy in the current epidemiological scenario.